Adeno-Associated Virus Type 2-Mediated Gene Transfer: Correlation of Tyrosine Phosphorylation of the Cellular Single-Stranded D Sequence-Binding Protein with Transgene Expression in Human Cells In Vitro and Murine Tissues In Vivo - Keyun Qing; Benjawan Khuntirat; Cathryn Mah; Dagmar Marie Kube; Xu-Shan Wang; Selvarangan Ponnazhagan; Shangzhen Zhou; Varavani Dwarki; Mervin C. Yöder; Arun Srivastava (1998)
ABSTRACT Although the adeno-associated virus type 2 (AAV)-based vector system has gained attention as a potentially useful alternative to the more commonly used retroviral and adenoviral vectors for human gene therapy, the single-stranded nature of the viral genome, and consequently the rate-limiting second-strand viral DNA synthesis, significantly affect its transduction efficiency. We have identified a cellular tyrosine phosphoprotein, designated the single-stranded D sequence-binding protein (ssD-BP), which interacts specifically with the D sequence at the 3′ end of the AAV genome and may prevent viral second-strand DNA synthesis in HeLa cells (K. Y. Qing et al., Proc. Natl. Acad. Sci. USA 94:10879–10884, 1997). In the present studies, we examined whether the phosphorylation state of the ssD-BP correlates with the ability of AAV to transduce various established and primary cells in vitro and murine tissues in vivo. The efficiencies of transduction of established human cells by a recombinant AAV vector containing the β-galactosidase reporter gene were 293 > KB > HeLa, which did not correlate with the levels of AAV infectivity. However, the amounts of dephosphorylated ssD-BP which interacted with the minus-strand D probe were also as follows: 293 > KB > HeLa. Predominantly the phosphorylated form of the ssD-BP was detected in cells of the K562 line, a human erythroleukemia cell line, and in CD34 + primary human hematopoietic progenitor cells; consequently, the efficiencies of AAV-mediated transgene expression were significantly lower in these cells. Murine Sca-1 + lin − primary hematopoietic stem/progenitor cells contained predominantly the dephosphorylated form of the ssD-BP, and these cells could be efficiently transduced by AAV vectors. Dephosphorylation of the ssD-BP also correlated with expression of the adenovirus E4orf6 protein, known to induce AAV gene expression. A deletion mutation in the E4orf6 gene resulted in a failure to catalyze dephosphorylation of the ssD-BP. Extracts prepared from mouse brain, heart, liver, lung, and skeletal-muscle tissues, all of which are known to be highly permissive for AAV-mediated transgene expression, contained predominantly the dephosphorylated form of the ssD-BP. Thus, the efficiency of transduction by AAV vectors correlates well with the extent of the dephosphorylation state of the ssD-BP in vitro as well as in vivo. These data suggest that further studies on the cellular gene that encodes the ssD-BP may promote the successful use of AAV vectors in human gene therapy.